In situ observation of successive crystallizations and metastable intermediates in the formation of metal-organic frameworks - Yeung, H; Wu, Y; Henke, S; Cheetham, A; O'Hare, D; Walton, R (Wiley, 2016)
Understanding the driving forces controlling crystallisation has important consequences ranging from the design of new materials to commercialisation. This is particularly relevant for metalorganic frameworks (MOFs), where mild solvothermal synthesis often allows access to related phases from the same reagents. Using high energy, in-situ synchrotron X-ray powder diffraction we have monitored the sequential crystallisations of three lithium tartrate MOFs, extracting the fundamental kinetic parameters of each interconversion. In particular, a rapidly-formed hydrated phase, 1, is transformed to a structurally-similar metastable anhydrous phase, 2a, with an activation energy of 41(3) kJ·mol^-1. Crystallization of the thermodynamic product, 2b, promotes dissolution of 2a but with a higher activation energy, 210(80) kJ·mol^-1. We have quantified the complete reaction energy profile of competing solvothermal crystallisations for the first time, and demonstrated new experimental and analytical methodology for the in-situ study of phase behaviour in the wider field of crystalline materials in general.